Chronic Kidney Disease and Urological Implications: The interplay between Chronic Kidney Disease and urological conditions - Shashi Kumar; N. Anil Kumar; C. Konda Reddy; Harsha Vardhana Varma Mudunuri (Orapuh Journal, 2024)
Introduction